2017
DOI: 10.1002/jhet.2877
|View full text |Cite
|
Sign up to set email alerts
|

A Simple One‐Pot Synthesis of Fully Substituted 1H‐Pyridone[1,2‐a]‐Fused‐1,3‐Diazaheterocycles

Abstract: An efficient procedure for the synthesis of 7‐(aryl)‐8‐nitro‐2,3,6,7‐tetrahydroimidazo[1,2‐a]pyridinones, 8‐(aryl)‐9‐nitro‐3,4,7,8‐tetrahydropyridone[1,2‐a]pyrimidines and 9‐(aryl)‐10‐nitro‐2,3,4,5,8,9‐hexahydropyridone[1,2‐a]diazepine via one‐pot three component reaction of diamine, nitroketene dithioacetal (1,1‐bis(methylsulfanyl)‐2‐nitroethene), and coumarine‐3‐ carboxylic acid derivatives in EtOH under reflux conditions is reported. The advantages of this procedure are simplicity, easy purification, good y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Meanwhile, Pyridone analogues have pharmaceutical and an extensive assortment of pharmacological efficacies [9]. They display antibacterial [10], antifungal [11], anti-HIV [12], anticancer activities [13]. Pyridones act through many mechanisms including inhibition of tyrosine kinases such as FGFR and VEGFR, Met and TAM family kinases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Pyridone analogues have pharmaceutical and an extensive assortment of pharmacological efficacies [9]. They display antibacterial [10], antifungal [11], anti-HIV [12], anticancer activities [13]. Pyridones act through many mechanisms including inhibition of tyrosine kinases such as FGFR and VEGFR, Met and TAM family kinases [14].…”
Section: Introductionmentioning
confidence: 99%
“…[18] A structure of ring fused with quinoxalines displays diverse pharmacological activities and has found applications in dyes, electron luminescent materials, and chemically controllable switches, as building blocks for the synthesis of anion receptors, cavitands, dehydroannulenes, and organic semiconductors, and as electrontransport materials in multilayer OLEDs. [25][26][27][28][29][30][31][32][33][34][35] Recently, Chen et al have reported a threecomponent domino reaction of HKAs with arylglyoxal monohydrates and β-diketone (like cyclohexane-1,3diones and 1,3-diphenylpropane-1,3-dione) for the synthesis of fused pyrroles. [20][21][22][23] To date, many works focus on the development of novel, MCRs, for constructing diverse and highly substituted fused heterocycles from available synthons heterocyclic ketene aminals (HKAs) with advantage for synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[24] HKAs have been used as bisnucleophiles to build fused heterocycles, because both the α-carbon and the secondary amino group can react with electrophiles. [25][26][27][28][29][30][31][32][33][34][35] Recently, Chen et al have reported a threecomponent domino reaction of HKAs with arylglyoxal monohydrates and β-diketone (like cyclohexane-1,3diones and 1,3-diphenylpropane-1,3-dione) for the synthesis of fused pyrroles. [36][37][38] To investigate the scope and limitations of this method and expand the diversity of the fused pyrrole library, another β-dicarbonyl compounds were used in this domino reaction.…”
Section: Introductionmentioning
confidence: 99%